The Inmate Assimilation Policy from a Political Perspective on National Security During the Covid 19 Pandemic - Aditya Romadhon; Arissy Jorgi Sutan; Zakly Hanafi Ahmad; M. Wira Anshori (Political Sciences Program Study, 2024)
The covid-19 pandemic has created a global crisis impacting various sectors, including national security. One of the Indonesian government’s responses to the pandemic was the inmate assimilation policy aimed at reducing the risk of virus transmission in overcrowded correctional facilities. This study employs a qualitative method with a literature review approach to analyze the inmate assimilation policy from a political perspective and its implications for national security. The findings indicate that the policy has significant implications for national security, raising concerns about increased crime rates within society. Key challenges in implementing this policy include economic crises, insufficient supervision, and social stigma against former inmates. Additionally, the policy highlights tensions between public health priorities and national security, where weak supervision can trigger social instability. Inadequate social reintegration further exacerbates the challenges faced by former inmates struggling to readjust. This study recommends the need for data-driven policy evaluations, enhanced inter-agency coordination, and strengthened social reintegration efforts to mitigate the policy's negative impact on social stability and national security in the future.